Giant Subgaleal cerebrospinal fluid leakage - Luis Rafael Moscote-Salazar; Hernando Raphael Alvis-Miranda; Amit Agrawal; Willem Calderon-Miranda; Alfonso Pacheco-Hernandez (Romanian Neurosurgery, 2017)
We report a rare case of chronic subdural hematoma complicated with a Giant subgaleal cerebrospinal fluid leakage. Physical examination was performed with no alteration in mental status and no focal neurological disorder. The subdural hematoma was drained and two weeks later, patient was admitted to our hospital with a giant scalp swelling. Physical examination revealed a left parietal subcutaneous collection. The patient was reoperated with a correction in the fistula, he presented a satisfactory postoperative evolution. To our knowledge, this is the first report in literature of a chronic subdural hematoma with a complicated giant subgaleal cerebrospinal fluid leakage.